Phytochemical Profiling of Ephedra alata subsp. alenda Seeds by High-Performance Liquid Chromatography—Electrospray Ionization—Quadrupole-Time-of-Flight-Mass Spectrometry (HPLC-ESI-QTOF-MS), Molecular Docking, and Antioxidant, Anti-diabetic, and Acetylcholinesterase Inhibition. (13th October 2022) - Mufti, Afoua; Tir, Meriam; Zarei, Armin; Contreras, María del Mar; Gómez-Cruz, Irene; Feriani, Anouar; Ghazouani, Lakhdar; Saadaoui, Ezzeddine; Allagui, Mohamed Salah; Harrath, Abdel Halim; Ramazani, Ali; Tlili, Nizar
Abstract: The aim of the current work was to study for the first time the phytochemical profile of Ephedra alata subsp. alenda seeds extract (ESS). The extract was characterized using high-performance liquid chromatography coupled to electrospray ionization quadropole time-of-flight mass spectrometry (HPLC–ESI–QTOF/MS). The antioxidant and antihemolytic properties were evaluated, and the inhibitory properties against α-amylase, α-glucosidase, and acetylcholinesterase were assessed. Chromatographic analysis revealed that ESS was rich in bioactive components including ephedrine derivatives, sphingolipides, flavonol, hexoside, and fatty acids. Furthermore, ESS displayed important antioxidant activity and α-glucosidase, α-amylase, and acetylcholinesterase inhibitory capacities. Moreover, ESS showed a preventive effect against oxidative stress induced hemolysis. In silico analysis confirmed the beneficial effects of ESS-phytochemicals. In fact, 3 out of the 14 investigated compounds, including isorhamnetin rutinoside, isoschaftoside, and kaempferol-3-rhamnoside, exhibited the best binding scores (less than −7) with two anti-diabetic targets. Isorhamnetin rutinoside also showed the highest number of hydrogen bonds with acetylcholinesterase highlighting its anti-cholieaterase potency. The current study suggested that seeds from E. alata are interesting sources of bioactive compounds and recommended as enzyme inhibitory agents in food and pharmaceuticals.